Place attachment to contemporary public-funded mosques in Malaysia - Najafi, Mina; Mohd Shariff, Mustafa Kamal (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Place is a Physical location formed by people’s relationship with physical environments, activities, and meanings. In this essence, Place Attachment is a concept that could describe the quality of the people’s relationship with a place. Although religion has a significant impact on the public place attachment within religious places, the architectural features and attributes of such physical settings could still play an influential role in leveraging this attachment. However, the role of architectural characteristics and features of Islamic religious places, as the components that make them meaningful, has not been adequately explored within the context of Malaysia. This paper reports the results of a conducted study for investigating Malaysian users’ attachment to five Malaysian mosques from three different architectural styles. The paper explains how Malaysian users attach to the mosques and which attributes of these places affect their attachment. In-depth interviews with 23 worshipers in the mosques and questionnaire survey with 288 people were conducted to address this objective. The study identified the drivers of Malaysian users’ attachment to the selected mosques. This study is a new approach to investigation of physical and ambient quality of mosques based on empirical data, hence providing theoretical basis for further investigations and improvements